Novel surgical procedure for the treatment of female stress urinary incontinence by using transobturator vaginal tape - Argirović Rajka; Likić-Lađević Ivana; Bošković Vladan; Berisavac Milica; Milenković Vera; Kadija Saša (Vojnosanitetski Pregled)
Introduction/aim: Current method in the treatment of female urinary incontinence implies the placement of tension-free suburethral vaginal tape, using a retropubic or transobturator approach. Considering numerous complications related to retropubic approach, we reported the results of transobturator procedure in prospective study. Methods. We used a non-absorbable polypropylene tape with the outside-in (Herniamesh) or in-outside (Johnson & Johnson) transobturator approach. Results. During the period from October 2004 to September 2005 the procedure was carried out in 10 patients. In only 2 cases urinary stress incontinence occurred as isolated problem managed with transoburator tape, whereas in 8 patients this procedure was associated with other operative gynecologic events. No perioperative complication was encountered. In 80% of the patients a satisfactory result was obtained, while one patient failed to demonstrate any amelioration, and the other developed subsequently urge incontinence. Conclusion. Transobturator tension-free vaginal tape represents a very simple, safe and, in the large percent of cases, successful procedure in the management of urinary stress incontinence, with rare perioperative complications.